Analysis of Teacher Behavior Errors in Learning - Handayani, Neni; Darsinah, Darsinah (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to analyze teacher behavior errors in learning at KB Mekar Sari, Ngargoyoso District, Karanganyar Regency . This research is a qualitative descriptive research with a case study type. The object of this research is teacher behavior in learning. Collecting data on teacher behavior in learning is obtained through observation . Data validation technique with technical triangulation . The data analysis technique used is the content analysis model . The results of the study show that there are errors in teacher behavior in learning , namely, the teacher is sometimes angry, the teacher often orders and forbids (3M) . Some teacher behaviors that should be carried out can be seen in the TBC ( Teacher Behavior Continuum ) stage or the continuum of teacher behavior in learning.